Lingkungan Keluarga Dan Motivasi Belajar Kontribusinya Terhadap Prestasi Belajar Akuntansi Pada Siswa Kelas X SMK Batik 2 Surakarta Tahun Ajaran 2016/2017 - Ayu Amelia, Windhie, Drs.Sudarto HS. MM (2017)
The purpose of this study was to determine: 1) the influence of family environment on learning achievement of accounting in class X SMK Batik 2 Surakarta, 2) the effect of learning motivation towards learning achievement of accounting in class X SMK Batik 2 Surakarta, 3) the influence of family environment and learning motivation towards learning achievement of accounting in class X SMK Batik 2 Surakarta. This type of research is quantitative associative. The population in this study were accounting students of class X SMK Batik 2 Surakarta with the number of 83 students. Samples were taken as many as 66 students using combination sampling that is proportional random sampling by a lottery. The data is obtained through a questionnaire and documentation that had previously been tested for validity and reliability. data analysis technique used is multiple linear regression analysis, F test, t-test, R2, effective contribution and relative contribution. Based on the data analysis obtained by multiple linear regression equation as follows : Y = 29.235 + 0.191 X1 + 0,605X2, the equation shows that the accounting student learning achievement influenced by the family environment and motivation to learn. Based on the analysis and discussion it can be concluded that: (1) the family environment is not effecting on learning achievement of accounting in Class X. it is prooved based on regression analysis which is obtained the value of tcount< ttable (1,210 <1.998) with significant value 0.231 > 0,05. (2) learning motivation effecting learning achievement of accounting in X Grade. It is prooved based on regression analysis which is obtained tcount> ttable (2.712 > 1.998), with significant value 0.009 <0.05. (3) the family environment and the learning motivation effecting on learning achievement of accounting in X grade. it is prooved based on regression analysis who received grades of fcount> ftable (5.311> 3.14) with significant value 0.007 <0.05 , (4) a family environment variables contribute effectively amounted to 54.30%. Learning motivation variables gives effective contribution amounted to 16.91%, with a coefficient of determination (R2) of 0.712, which means 71.2% of the learning accounting achievements variation is explained by the family environment and learning motivation, and the remaining 28.8% is explained by other variables outside researched.